PENGARUH E-COMMERCE SHOPEE DAN KEMUDAHAN BERTRANSAKSI TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA FAKULTAS EKONOMI BISNIS ISLAM UIN RADEN INTAN LAMPUNG - Fakhri Dani Alfarizi (Business and Enterpreneurship Journal (BEJ), 2023)
This study aims to determine the effect of e-commerce shopee and ease of transaction on student consumptive behavior. The data used is primary data. Furthermore, the data collection technique used in this study was distributing questionnaires to respondents who used the Google form to collect data. In this study the researchers used the t test method and coefficient test with the help of the smart pls program version 3. Based on the results of the research the R² value lies at 0 R² 1, an R² value close to one which means the model is getting better. Meanwhile, the value of R² which is zero means that there is no relationship between the dependent variable and the explanatory variable. From the table with the location of R² 1 with a value of 0 0,270 1, this means that the variance of e-commerce shopee and ease of transaction can explain the variance of consumer behavior by 100%.Keywords: E-Commerce, Ease of Transaction, Consumptive Behaviour